The EOQ Model: A Differential Cyclic System for Calculating Economic Order Quantity - Rabha Ibrahim; Samir Hadid (International Journal of Analysis and Applications, 2018)
The EOQ model determines the quantity that minimizes the total sum of all cost functions. We suggest a common structure for economic order quantity type non-linear differential models with costs functions with respect to time in a cyclic period. For this model, we analyze the related optimization problem and develop a relaxed method for determining a bounded interval containing the optimal cycle length. Also for a special class of transportation functions, we study these consequences and introduce algorithms to calculate the optimal size and the corresponding optimal order stage.